2013
DOI: 10.4236/ajps.2013.49229
|View full text |Cite
|
Sign up to set email alerts
|

<i>Elaphoglossum</i> (Dryopteridaceae-Fern) of Amazon Rainforest in Brazil: Anatomic Characterization and Adaptative Strategies

Abstract: This study describes the anatomy of sterile leaves of Elaphoglossum discolor (Kuhn) C. Chr., E. flaccidum (Fée) T. Moore and E. laminarioides (Bory ex Fée) T. Moore, the most representative species of the genus in the Ecological Park of Gunma in Pará State. It reports the main diagnostic characters and provides new systematic data for the group. In addition, it locates the production and accumulation sites of bioactive compounds to determine possible adaptive strategies of these species in the Amazon rainfores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…The present study was initiated to determine whether leaf epidermal anatomical data, that is, size and shape of epidermal cells, stomatal size and pattern, and spore morphological data might shed light on the relationships of Asplenium species. The use of taxonomic characters of leaf epidermis, that is, epidermal cells and mature stomata is not new, and its taxonomic importance is evident in several studies on ferns (Bondada et al, 2006; Bruce, 1976; Chandra & Hashim, 1974; Chuang & Liu, 2003; Feio et al, 2013; Inamdar et al, 1971; Kato & Imaichi, 1992; Lee & Oh, 1988; Libing, 1996; Mickel & Votava, 1971; Nayar, 1962; Pant & Khare, 1969; Sen & Hennipman, 1981; Sen & Mukhopadhay, 2011; Shah et al, 2019a; Shah, Ahmad, Zafar, Malik, et al, 2018; Shah, Ahmad, Zafar, Razzaq, et al, 2018; Sundue, 2009; Thurston, 1969; Van Cotthem, 1970a, 1970b; Viane, 1990; Viane & Van Cotthem, 1977; White, 1974; Yang & Zhang, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was initiated to determine whether leaf epidermal anatomical data, that is, size and shape of epidermal cells, stomatal size and pattern, and spore morphological data might shed light on the relationships of Asplenium species. The use of taxonomic characters of leaf epidermis, that is, epidermal cells and mature stomata is not new, and its taxonomic importance is evident in several studies on ferns (Bondada et al, 2006; Bruce, 1976; Chandra & Hashim, 1974; Chuang & Liu, 2003; Feio et al, 2013; Inamdar et al, 1971; Kato & Imaichi, 1992; Lee & Oh, 1988; Libing, 1996; Mickel & Votava, 1971; Nayar, 1962; Pant & Khare, 1969; Sen & Hennipman, 1981; Sen & Mukhopadhay, 2011; Shah et al, 2019a; Shah, Ahmad, Zafar, Malik, et al, 2018; Shah, Ahmad, Zafar, Razzaq, et al, 2018; Sundue, 2009; Thurston, 1969; Van Cotthem, 1970a, 1970b; Viane, 1990; Viane & Van Cotthem, 1977; White, 1974; Yang & Zhang, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…According to several, floristic and taxonomic studies (Nakaike & Malik, 1992, 1993Stewart, 1967;Stewart, Ali, & Nasir, 1972), the following species are recognized for the study region Malakand division: Asplenium adiantum-nigrum L., Asplenium × alternifoliumWulfen., Asplenium fontanum (L.) Bernh. The importance of leaf micromorphology to ferns taxonomy and systematics is well established (Nayar, 1962;Pant & Khare, 1969;Thurston, 1969;Van Cotthem, 1970b;Inamdar, Patel, & Bhatt, 1971;Mickel & Votava, 1971;Chandra & Hashim, 1974;White, 1974;Bruce, 1976;Viane & Van Cotthem, 1977;Sen & Hennipman, 1981;Lee & Oh, 1988;Viane, 1990;Kato & Imaichi, 1992;Libing, 1996;Chuang & Liu, 2003;Yang & Zhang, 2003;Bondada, Tu, & Ma, 2006;Sundue, 2009;Sen & Mukhopadhay, 2011;Feio, de Aguiar-Dias, & de Vilhena Potiguara, 2013;Shah, Ahmad, Zafar, Razzaq, et al, 2018;Shah et al, 2019a). Asplenium L. is attracting interest of several investigator not only of its morphology but also for several aspects of anatomy (Bercu, 2005;Chaerle & Viane, 2004;Hayata, 1927;Khare & Shankar, 1989;Mitsuta, Kato, & Iwatsuki, 1980;Nopun, Traiperm, Boonkerd, & Jenjittikul, 2016;Schneider, 1997;Umikalsom, 1992;Wetzel, Sylvestre, Barros, & Vieira, 2017).…”
mentioning
confidence: 99%
“…Segundo Feio et al (2013) estes compostos possuem propriedades peculiares relacionadas a herbivoria e evasão de patógenos em Elaphoglossum laminariodes (Fée) T. Moore, demonstrando que a espécie é adaptada ao seu ambiente, produzindo metabólitos secundários diretamente relacionados ao seu sucesso adaptativo. Ainda de acordo com esses autores os compostos mucilaginosos encontrados exclusivamente nessa espécie, servem para reter água, uma vez que a mesma ocorre em áreas expostas ao sol.…”
Section: Resultsunclassified
“…De acordo com Feio et al (2013) a estrutura vascular do pecíolo de Elaphoglossum discolor (Kuhn) C. Chr., E. flaccidum (Fée) T. Moore e E. laminarioides (Fée) T. Moore (Samambaias) foi semelhante ao descrito para a nervura central dos taxa.…”
Section: Resultsunclassified
“…Phenolic compounds are usually related to different adaptive strategies like protection against drying and attack by animals (Feio et al 2013), being commonly found in ferns (Ogura 1972) and xerophytes from other plant groups (Pyykkö 1966). In both groups, their production increases under unfavorable conditions, therefore acting as a stress bioindicator (Siddiqui & Arif-uz-Zama 2004, Achakzai et al 2009.…”
Section: An Acad Brasmentioning
confidence: 99%